Mechanical, thermal, and morphological properties of poly(lactic acid) (PLA)/ recycled tyre rubber waste compatibilised with chain extender - Qasem, Ramzi; Mohd Bijarimi, Mat Piah; Alhadadi, Waleed (Universiti Malaysia Pahang, 2023)
The accumulation of waste tires in our society is a pressing issue due to their short lifespan and increasing demand. This research delves into effective methods for recycling waste tires, with a particular focus on utilising biopolymers. Polylactic acid (PLA), a completely biodegradable polymer, has gained popularity for its biocompatibility, biodegradability, mechanical strength, and ease of processing. To overcome its toughness and thermal stability limitations, PLA has been blended with commercial polymers, such as rubber. Furthermore, the addition of 10% recycled tyre waste to 90% PLA has been shown to increase its durability and strength. Joncryl® ADR is used as a chain extender and reactive compatibiliser to enhance the chemical interactions in the binary blend. The samples were prepared using a twin-screw extruder with the temperature between 150 and 190 ºC and 60 rpm of screw speed. These blends are then analyzed using a range of characterization techniques, including Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), scanning electron microscopy (SEM), tensile testing, and notched Izod impact testing. The blends were then characterized by chemical changes, thermal transitions, and thermal degradation. It was found that the 90/10/0.6 (PLA/RW/ADR) nanocomposite exhibited maximum thermal degradation.